Effect of Passing Plays on Injury Rates in the National Football League. (December 2021) - Burke, Jonathan; Geller, Joseph S.; Perez, Jose R.; Naik, Kunal; Vidal, Armando F.; Baraga, Michael G.; Kaplan, Lee D.
Abstract: Burke, J, Geller, JS, Perez, JR, Naik, K, Vidal, AF, Baraga, MG, and Kaplan, LD. The effect of passing plays on injury rates in the national football league. J Strength Cond Res 35(12S): S1–S4, 2021—The National Football League (NFL) has one of the highest all-cause injury rates in sports, yet our understanding of extrinsic injury risk factors is limited. The objective of this study was to assess the effect of play type on injury incidence in the NFL. We obtained data for every regular season game played during the 2013–2016 seasons from the official NFL game books. There were 2, 721 in-game injuries during the 4 seasons examined, with an overall rate of 1.33 injuries per team per game. For statistical analysis, p < 0.05 was considered significant. Passing plays conferred significantly higher odds of injury than running plays (odds ratio [OR] 1.4, 95% confidence interval [CI]: 1.3–1.5, p < 0.0001). This primarily stems from increased risks in quarterbacks (OR 6.9, 95% CI: 3.6–13.3, p < 0.0001), receivers (OR 5.0, 95% CI: 3.7–6.6, p < 0.0001), and defensive backs (OR 2.3, 95% CI: 1.9–2.7, p < 0.0001). Our study suggests that passing plays confer a greater risk of overall injuries in the NFL when compared with running plays, specifically regarding concussions and core or trunk injuries.